An Analytical Recap of Nanotechnology for Dental Applications (International Journal of Food and Nutritional Sciences, 2022)
Biological nanotechnology applications have advanced significantly during the past few generations. Nanomaterials have a proven track record in several dental applications, strengthening of polymeric composites, endodontic uses, involving tissue repair, and implantation coatings. The development of new nano-biomaterials and the modification of the characteristics of currently existing biomaterials have raised the bar for oral health care standards. To envision the future of dentistry, one must have a better understanding of nanotechnology. These intriguing materials are anticipated to find several dental applications with better therapeutic uses during the next ten years. This stud’s goal is to go through the existing uses of nano-biomaterials in dentistry, as well as recent advancements and possible prospects.